ANALISIS KUALITAS WEBSITE SAMSAT JAMBI MENGGUNAKAN METODE DELONE AND MCLEAN - Maria Rosario B; Marrylinteri Istoningtyas; Fitria Febrianti (LPPM Universitas Abdurrab, 2021)
The SAMSAT website is an application of information technology that is used to facilitate motorized vehicle users to obtain information related to services provided by the SAMSAT office. Based on the results of the initial questionnaire that the researcher has distributed to 50 respondents, 82% of the respondents stated that the SAMSAT Jambi website has weaknesses, including the website is less attractive in terms of interface and there is an error menu on the website. The purpose of this study is to analyze the level of success of the website SAMSAT Jambi using the Delone and Mclean method and to determine the effect of independent variables (system quality, information quality, service quality) on the dependent variable (use, user satisfaction, net benefits). Data analysis using SEM and SmartPLS software. Based on the results of the data processing of the Jambi community questionnaire, it was found that of the 9 hypotheses proposed in this study, only 7 hypotheses were acceptable including system quality on usage, system quality on user satisfaction, quality of information on usage, quality of information on user satisfaction, use of user satisfaction, use of net benefits, and user satisfaction with net benefits